IMPLEMENTASI METODE BEST WORST METHOD UNTUK PENILAIAN KARYAWAN TERBAIK BERDASARKAN KRITERIA MULTI-ASPEK PADA BENGKEL KARYA JOK - Erna, Fadil; Endar Nirmala (Teknik Informatika Universitas Pamulang, 2025)
The selection of the best employees is a crucial aspect of human resource management that requires an objective and efficient approach. This study aims to implement the Best Worst Method (BWM) in a decision support system to evaluate the best employees based on various multi-aspect criteria at Bengkel Karya Jok. The BWM method is used to determine the weight of each criterion based on managerial preferences, resulting in a more structured and accurate employee ranking. The evaluation is conducted by comparing the ranking results obtained from the system with conventional methods previously used. Testing is carried out using employee data from Bengkel Karya Jok, while validation is performed through comparative analysis of results and user questionnaires. The findings indicate that the BWM method enhances objectivity and transparency in employee evaluation, assisting management in making more effective decisions. Additionally, the implementation of a technology-based system improves efficiency and accessibility in the selection process. The conclusion of this study suggests that the implementation of the BWM method can be an optimal solution for employee evaluation based on multi-aspect criteria. The results of this study are expected to serve as a reference for similar industries in adopting a more systematic and accurate decision support system.